2005
DOI: 10.1590/s0066-782x2005000500007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de fatores de risco cardiovascular em crianças e adolescentes da rede de ensino da cidade de Maceió

Abstract: The prevalence of a sedentary lifestyle, "risk of overweight," overweight, systemic arterial hypertension, and smoking in the population studied was 93.5%, 9.3%, 4.5%, 7.7%, and 2.4%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
57

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 45 publications
2
44
1
57
Order By: Relevance
“…The present study identified 52.4% of the sample as having initial arterial pressure equal to or higher than the ninetieth percentile. Furthermore, another study (17) identified a prevalence of the order of 7.7% among students aged 7 to 17 with arterial pressure equal to or higher than the ninety-fifth percentile, similar to the study carried out in the city of Fortaleza in the state of Ceará, where the prevalence of 52.4%…”
Section: Discussionsupporting
confidence: 73%
“…The present study identified 52.4% of the sample as having initial arterial pressure equal to or higher than the ninetieth percentile. Furthermore, another study (17) identified a prevalence of the order of 7.7% among students aged 7 to 17 with arterial pressure equal to or higher than the ninety-fifth percentile, similar to the study carried out in the city of Fortaleza in the state of Ceará, where the prevalence of 52.4%…”
Section: Discussionsupporting
confidence: 73%
“…In ten studies, the sample was school-based 16,17,18,19,20,21,22,23,24,25 and four included workers 26,27,28,29 . The sample size ranged from 160 individuals 30 to 54,369 8 , while the majority of the studies (38) included more than a thousand subjects, and only two included fewer than five hundred 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…In all, 20 studies included adolescents (10-17 years), of which tem included only this age bracket. Only two studies included children (7-9 years) in the sample 20,21 , neither of which exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…8,12,13 Some studies have shown direct correlation between increased incidence of cardiovascular disease and total cholesterol levels above 200 mg/dl. 9,14,15 In our study, we observed increased levels of this lipid, reaching a peak in the middle age group (41-60 years) and suffering a slight fall in the age group of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Keeping this in mind, it becomes necessary to analyze the epidemiological profile for effective prevention and treatment of this disease.…”
mentioning
confidence: 99%